Assessing the Economic Value of Water Environmental Services in Mount Merbabu National Park - Dewi, Kristina; Hardian, Andi Syamsu; Cahyono, Sigit Andy (Department of Forestry, Faculty of Agriculture, University of Lampung, 2024)
Mount Merbabu National Park (MMNP) is a conservation area that provides environmental services (water) to surrounding villages spread across its area; however, the community has not realized its essential role. The study aims to calculate the economic benefits of water environmental services in MMNP, which the surrounding community utilizes for household needs. Primary data collection was conducted by interviews using structured questionnaires. Samples were determined using the purposive sampling method on 39 MMNP water sources. Data analysis was carried out by calculating public perceptions of water use and assessing willingness to pay for water use for household needs. The study results showed that the economic value of household water is IDR 10,700,681,768 per year, with the value of the willingness to pay the community for water utilization and conservation IDR 4,360,408,000 per year. The total economic benefit of water in the MMNP area is IDR 15,061,089,768 per year. The views and dynamics of water source management on Mount Merbabu are diverse. The water on Mount Merbabu has been a blessing, a source of conflict, a source of life, and can be a tool of political intimidation. It is necessary to make the public aware of water sources, recharge areas, and better water utilization because water has economic value. Keywords: economic value, environmental services, Mount Merbabu National Park, water, willingness to pay